The Chemical Compositions of Thermal Waters at Ciarinem and Cilayu, Pameungpeuk, West Java - Indonesia - N. R. Herdianita; B. Priadi (Institute for Research and Community Services (LPPM) ITB, 2008)
Thermal waters at Ciarinem and Cilayu, Pameungpeuk, West Java, Indonesia have different characteristics: Ciarinem water is a steam heated sulfate type and occurs as hot springs, whereas Cilayu water discharges as hot pools and is a chloride water type. Their chemical compositions indicate that the thermal waters are outflows of a volcanic